Analisis Tingkat Implementasi Good Corporate Governance Pada PT. Bank Aceh Syariah KC Bireuen - M. Iqbal; Farhan Miswari; Gina Fadhila; Siti Sofia Sari; Rifdah Atika Pasaribu (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This article aims to analyze the level of implementation of good corporate governance (GCG) at PT. Bank Aceh Syariah KC Bireuen through a qualitative approach using the interview method. Qualitative research methods are used to gain an in-depth understanding of GCG practices in Islamic financial institutions. This research involved interviews with parties related to the organization, one of whom was the bank's staff. The data collected was analyzed to evaluate the extent to which GCG has been implemented in various aspects of the company, such as Transparency (Information Openness), Accountability (Accountability), Responsibility (Accountability), Fairness (Fairness), Professional, Shariah Compliance. The results of this analysis are expected to provide a comprehensive picture of the level of GCG implementation at PT. Bank Aceh Syariah KC Bireuen and potential improvements that can be made. This research is expected to contribute to stakeholders in understanding the importance of GCG in improving company performance and public trust.